2014
DOI: 10.1007/s00204-014-1447-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of silver nanoparticles (AgNPs) on the cardiovascular system

Abstract: With the advent of nanotechnology, the use and applications of silver nanoparticles (AgNPs) have increased, both in consumer products as well as in medical devices. However, little is known about the effects of these nanoparticles on human health, more specific in the cardiovascular system, since this system represents an important route of action in terms of distribution, bioaccumulation and bioavailability of the different circulating substances in the bloodstream. A collection of studies have addressed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 87 publications
1
33
0
Order By: Relevance
“…AgNPs have been employed in the treatment of cardiovascular diseases, neurodegenerative diseases, brain inflammation, neurotoxicity and diabetes etc. [3][4][5]. AgNPs have been widely used as antifilarial, antiinsecticidal, antilarvicidal, antiprotozoal and anticandidal agents [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AgNPs have been employed in the treatment of cardiovascular diseases, neurodegenerative diseases, brain inflammation, neurotoxicity and diabetes etc. [3][4][5]. AgNPs have been widely used as antifilarial, antiinsecticidal, antilarvicidal, antiprotozoal and anticandidal agents [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…2 Biology and Toxicology Division, CSIR-IICT, Hyderabad, Telangana, India. 3 Department of Chemistry, Yogivemana University, Kadapa, Andhra Pradesh, India. 4 DST-PURSE Center, Sri Venkateswara University, Tirupati, Andhra Pradesh, India.…”
Section: Introductionmentioning
confidence: 99%
“…The ENMs can enter the body through various ways, e.g., inhalation, ingestion, skin uptake, injection, implantation, and direct penetration in cells and tissues ( Figure 1) [17]. Among these, inhalation and injection are the most common ways of exposure.…”
Section: The Exposure Routes Of Enms and Their Distribution In The Kimentioning
confidence: 99%
“…The adverse effects of Ag NPs on the cardiovascular system are still debated [106][107][108]. It is also possible to use different exposure routes to investigate the nano-toxic potentials of Ag NPs on the cardiovascular system [109]. Tang et al (2009) reported that Ag NPs could transit directly to the cardiovascular system and cause adverse effects by accumulating in various organs [110].…”
Section: In Vivo Toxicological Information and Experiments About Silvmentioning
confidence: 99%